John Keats as a Poet of Sensuousness: Exploring Sensuousness in John Keats' Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2016)
It goes without saying that John Keats belongs to the younger generation of Romantic poetry who is primarily known for his sensuous expressions in his poetry His ode poetry speak volumes of his highest poetic achievement, and are the best specimen of sensuous poetry ever in the history of English literature. A minute observation of john keats’ poetry shows how the poet uses his images and things of nature presenting sensuousness. There is no doubt in denying the fact that the poet is particularly successful in depicting the reality as his poetry manifests a kind of concreteness which has the capability of convincing the readers. On the whole, Keats’ poetry is abundantly rich in sensuousness, suggestiveness and freshness, and the vision of beauty perceived by the poet has the finest essence of what he senses gather from his environment.